Depression, anxiety symptoms, and association with household characteristics in adolescent boys and girls from Matiari District, Pakistan: A community-based cross-sectional study - Florence Perquier; Susan C. Campisi; Clare Zasowski; Katherine Tombeau Cost; Yaqub Wasan; Sajid B. Soofi; Mina Husain; Daphne Korczak; Suneeta Monga; Peter Szatmari; Zulfiqar A. Bhutta (PLoS ONE, 2026)
Introduction Pakistan has one of the world’s largest adolescent populations, yet evidence on the prevalence and correlates of depressive and anxiety symptoms in adolescents remains limited, particularly in rural settings. Objective This study aimed to estimate the prevalence of depressive and anxiety symptoms and examine their associations with household characteristics in a community-based sample of adolescents from the predominantly rural district of Matiari, Pakistan. Methods We examined cross-sectional data from 718 girls (9.0–14.9 years) and 678 boys (10.0–15.9 years) participating in the Nash-wo-Numa Study. Trained psychologists administered the Sindhi versions of the Short Mood and Feelings Questionnaire and the Screen for Child Anxiety Related Emotional Disorders to assess adolescents’ depressive and anxiety symptoms. Prevalence estimates and 95% confidence intervals were derived based on validated cut-off scores. Household correlates of depressive and anxiety symptoms were examined in multivariable negative binomial regression models. Results Approximately 8% of boys and 10% of girls exhibited clinically-significant depressive symptoms. The prevalence of clinically-significant anxiety symptoms ranged from 6% in boys and 8% in girls for generalized anxiety to 24% in boys and 39% in girls for separation anxiety symptoms. Girls experienced more depressive symptoms, panic/somatic and generalized anxiety symptoms than boys at age 12, more separation anxiety symptoms from age 11 onward, and more social anxiety symptoms from age 12 onward. In both sexes, depressive and anxiety symptoms were higher among adolescents exposed to intimate partner violence against their mothers and to moderate‑to‑severe food insecurity, and were lower among those with a homemaker mother. Among girls, maternal mental well‑being attenuated the association between food insecurity and depressive symptoms. Conclusion Depressive and anxiety symptoms are common among adolescents living in Matiari. Adolescents exposed to intimate partner violence against their mother, moderate-to-severe food insecurity, and poor maternal mental health may be at increased risk of depression and anxiety in predominantly rural Pakistan and may benefit from targeted prevention and intervention strategies.